WAR on Terrorism: Impact on Pakistan’s Economy - Rehana Saeed Hashmi (Journal of Political Studies, 2007)
In analyzing the government of Pakistan’s policies towards USA in the war against terrorism, this article focuses on Pakistan US relationship and US assistance to Pakistan for economic development. The main concern is to understand the environment of mistrust between the two states and need to analyze that Pakistan’s economic development should be based on sound long term economic policies. In the region of South Asia, Pakistan has the most delicate strategic position. The event of Russian invasion in Afghanistan during cold war period and in the post cold war era, the other world shaking event, the terrorist attacks on World Trade Centre have witnessed that these developments profoundly affected Pakistan’s strategic position. The incident of 9/11 affected Pakistan’s defence and strategic concerns, its national cohesion, domestic stability and economic condition.